The Indonesian Government’s Incapable Reliance on Private Islamic School Owners in Upholding The Nation’s Principles - Nur Kholis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2022)
This article examines the role of private Islamic schools in Indonesia in providing education and fostering religious values among their students. It argues that the Indonesian government has failed to ensure equal access to quality education for all citizens and to instill a strong sense of religious identity in them. The objective of the article is to highlight the strategies employed by private Islamic schools in building students' religious character, which is seen as an essential component of their education. The article adopts a qualitative method with a multiple-case study approach on three private Islamic schools in Pekalongan, a city known for its Islamic culture and tradition. The article identifies three main strategies that the school foundation management uses to nurture students' religious character: daily supervision, monthly guidance session, and warm personal communication. The article concludes with a recommendation that the government should recognize and support the contribution of private Islamic schools in developing their own curriculum that reflects their religious vision and values.